Effects of childhood adversity trajectories on mental health outcomes in late adolescence: The buffering role of parenting practices in Taiwan. (November 2020) - Lee, Miaw-Chwen; Huang, Nicole; Chen, Chuan-Yu
Abstract: Background: Childhood adversities (CAs) have been linked with unfavorable development; however, the chronic trajectories of multiple CAs and possible heterogeneous effects are understudied. Objectives: This study examined the trajectories of multiple CAs and their associations with mental health outcomes in adolescence and investigated the buffering effect of parenting practices. Participants and setting: We used population-representative data from the Taiwan Education Panel Survey (2005 and 2007, n = 10, 416). Methods: This study was based on retrospectively self-reporting of six CAs, namely physical abuse, family economic hardship, parental problematic drinking, parental catastrophic health problems, parental divorce, and parental death, at three developmental periods: early childhood, middle childhood, and early adolescence. Group-based multitrajectory modeling and multiple regressions were used to identify distinct trajectories of multiple CAs and evaluate the association estimates. Results: A total of four trajectory groups were identified: increasing family economic hardship (12.3 %), chronic physical abuse (3.3 %), chronic parental problematic drinking (2.8 %), and low adversity (81.6 %). The chronic physical abuse group had the highest levels of depressive symptoms (β = 6.61, p < .001) and suicidal ideation (Adjusted Odds Ratio [AOR] = 2.67, p < .001), whereas the chronic parental problematic drinking group had the highest level of substance abuse (AOR = 4.59, p < .001). Positive parental practices buffered the harmful effects of increasing family economic hardship in late adolescence, particularly for depressive symptoms and substance abuse. Conclusions: Adverse mental health outcomes varied among groups with distinct multiple CA trajectories. The provision of social services to train or support positive parenting practices in families experiencing economic hardship is a potentially valuable resilience strategy.